Analysis The Causes of Bad Credit: Literature Review - Sasmiharti, Juni (PT. Maju Malaqbi Makkarana, 2024)
Bad credit is one of the main problems faced by the banking sector, which can threaten financial stability and bank profitability. This research aims to analyze the causes of bad credit through the literature review method, by identifying and evaluating relevant scientific works. The research results show that the causes of bad credit can be categorized into four main factors: internal factors of the borrower, external factors of the borrower, internal factors of the bank, and regulatory and policy factors. The borrower's internal factors include poor management and weak financial capabilities, while external factors include unstable macroeconomic conditions and intense business competition. Internal bank factors include weak credit assessment processes and inappropriate credit policies, while regulatory and policy factors include less effective regulations and erratic changes in government policy. To reduce the risk of bad credit, banks and financial institutions are advised to improve credit assessment processes, tighten supervision of the use of funds, develop credit policies that are more flexible but based on in-depth risk analysis, and strengthen regulations and supervision. Macroeconomic risk mitigation strategies are also important to maintain financial stability. By implementing these strategic steps, it is hoped that the risk of bad credit can be minimized, support the stability and sustainability of the banking sector, and increase trust and security for all parties involved. This research emphasizes the importance of a comprehensive and coordinated approach in credit risk management to ensure the sustainability and stability of the financial system.